China the pessoptimist nation - Callahan, William A. (Oxford : Oxford University Press, 2010)
China is fast becoming the next superpower - a rise that presents a challenge to the world economically, politically and culturally. Drawing on extensive new Chinese sources, Professor Callahan sheds light on how Chinese people understand their changing place, and what that might mean for the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: China -- Foreign relations -- 21st century; China -- Politics and government; China -- Social conditions; China -- Social conditions -- Public opinion; Public opinion -- China; China -- Foreign public opinion